Examining the genetic diversity and genetic structure of Dysosma difformis in the northern region of Vietnam using Inter-Simple Sequence Repeat Markers (ISSR) - Nguyen, Duc Hieu; Le, Thi Tuoi; Nguyen, Thi Tam; Nguyen, Dinh Trong; Pham, Bich Ngoc; Chu, Hoang Ha; Tran Ho, Quang (Vietnam Journal of Biotechnology, 2025)
The restricted distribution range of rare medicinal plants can largely be attributed to unscientific harvesting practices and the high societal demand for pharmaceuticals and health supplements. One of the outstanding cases is the Dysosma genus, which is reported to have numerous species endemic to China. Many studies indicate that these species typically have small wild populations, leading to significant challenges. These small populations face intense pressure from natural selection, genetic drift, and a potential reduction in genetic diversity. In this research, we assess the genetic diversity of Dysosma difformis populations by applying Inter-Simple Sequence Repeat markers (ISSR). The findings reveal considerable outcomes, with Shannon’s genetic index (I) of 0.538, Nei's genetic diversity (H) of 0.3658, gene flow (Nm) of 1.0604, and genetic differentiation among populations of GST = 0.3204. The genetic distances among populations varied, with a minimum of 0.0645 (Phu Tho and Ba Vi) and a maximum of 0.3901 (Phu Tho and Lai Chau). The study's findings revealed that D. difformis in northern Vietnam exhibits significant genetic diversity, even with a small population size. Furthermore, we discovered that the D. difformis populations in Phu Tho and Ba Vi are genetically closely related, suggesting they likely share a common evolutionary origin despite being located in two distinct geographical areas that are adjacent to each other. Furthermore, this study provides insights into the genetic structure and evolutionary origin of D. difformis populations in northern Vietnam. Additionally, this information is also crucial for conservationists to support genetic breeding initiatives and preserve the diversity of D. difformis.